ACKNOWLEDGING PEERS DURING DISAGREEMENTS - Zuliati Rohmah (TEFLIN Journal: A publication on the teaching and learning of English, 2007)
This article describes strategies to promote collaboration applied by students when expressing disagreements. By using Conversational Analysis (CA), the researcher collected and analyzed data from fourteen doctorate classroom discussions. The results show that the students applied four ways of acknowledging peers during disagreements. Suggestions are put forward at the end of the article.